1979
DOI: 10.1007/bf00117153
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the equation of state of solid hydrogen and deuterium at high pressures

Abstract: Isochores of solid hydrogen and deuterium have been measured for melting line pressures up to 2000 bar. These are corrected to correspond to para-H2 and ortho-D2. The 4.2 K isotherm of H2 has been determined and compared to the extrapolated low-pressure isochore of Anderson and Swenson (AS). Deviations have led us to reanalyze the AS data. The 4.2 K isotherm and the isochores are used, with the aid of a Mie-Griineisen analysis, to determine P-V-T data for these solids up to 25 kbar. An analysis is presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
27
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 46 publications
7
27
0
Order By: Relevance
“…25 in comparison with density-functional theory (DFT)-generalized gradient approximation (GGA) calculations [26] and the main experimental results from [3,5,[7][8][9][10]12,13,16]. It was shown that the semi-empirical (SE) calculations with the proposed many-body potential are in an excellent agreement with experiment in the pres-sure range 1-140 GPa (phases I and II).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…25 in comparison with density-functional theory (DFT)-generalized gradient approximation (GGA) calculations [26] and the main experimental results from [3,5,[7][8][9][10]12,13,16]. It was shown that the semi-empirical (SE) calculations with the proposed many-body potential are in an excellent agreement with experiment in the pres-sure range 1-140 GPa (phases I and II).…”
mentioning
confidence: 86%
“…The central characteristics of every substance is equation of state (EOS) which is a basis for studying all physical properties of the substance, in particular for developing and examining model intermolecular potentials and testing ab initio theories. Systematic high-pressure studies of the EOS of solid hydrogens were started in the 1970s [1][2][3][4][5][6], and at present they reach the pressures up to ~2 Mbar [7][8][9][10][11][12][13]. The highest volume compression reached in the EOS experiments is 10.4 for solid hydrogen [13] (7.6 for solid D 2 [12]), higher than for solid helium (8.4) [14].…”
mentioning
confidence: 99%
“…Close to the equilibrium density the H 2 kinetic energy is 89.5 K, which roughly amounts to half of the potential energy. In comparison to solid 4 He, in which both types of energies are nearly equal, quantum nuclear effects in solid hydrogen turn out to be smaller (see also (Driessen, de Waal, and Silvera, 1979). From Osychenko, Rota, and Boronat (2012).…”
Section: B Hydrogenmentioning
confidence: 99%
“…They attributed the effect to a solid phase transition. For a time, the proposed explanation drew some criticism [13,14], but supporting evidence was later obtained from detailed measurements of the hydrogen melting line [24]. A small cusp-like singularity was observed near 14 K and interpreted as the intersection point of the solidsolid phase line.…”
Section: Cp(tp)mentioning
confidence: 96%
“…An analytic form for (aPlaT), can be derived in either of two ways: eq (8a) can be inverted to express the pressu;e as a function of temperature and volume, and the desired function is obtained by differentiation. Or, the result can be calculated directly from the identity ( ap) a aT ,""'p (14) and eqs (9) and (11). In either case, we estimate an uncertainty of ±2% for this calculated quantity.…”
Section: Other Related Datamentioning
confidence: 99%